Extent of resection and radiotherapy in GBM: A 1973 to 2007 surveillance, epidemiology and end results analysis of 21,783 patients - ZINN, PASCAL O; COLEN, RIVKA R; KASPER, EKKEHARD M; BURKHARDT, JAN-KARL (International journal of oncology, 2013)
Surgery, radiation and chemotherapy are the standard of care for GBM patients, however, the impact of extent of resection (EOR) and radiotherapy (RT) on patient survival across age groups has not been established. Therefore, we present the current largest study on EOR and RT in GBM over the past three decades. Using the population based Surveillance, Epidemiology and End Results (SEER) registry, we identified a total of 21,783 GBM patients (1973-2007). Survival analysis based on EOR and RT was performed by means of factor analysis, Kaplan-Meier survival and Cox proportional hazard's ratio. Age, RT and EOR were highly prognostic (p<0.00001). Combined gross total resection (GTR) and RT showed the longest median survival (11 months) compared to subtotal resection (STR) and RT (9 months). Survival times after monotherapy with RT, GTR and STR were 5, 3 and 2 months, respectively. Patients without therapy showed a median survival of 1 month. RT and GTR demonstrated highest median survival. Interestingly, survival advantage of GTR versus STR amounted to only 1-2 months. Monotherapy (GTR, STR or RT) showed a significantly lower survival rate compared to combination therapies. RT alone yielded significantly better survival compared to any resective approach. Relative to overall age-specific median survival, elderly patients still reasonably benefit from RT alone. However, across all age groups multimodality treatment with surgery and RT continues to provide the largest survival benefit compared to either treatment alone and, thus, should be pursued whenever feasible.